2022
DOI: 10.3390/biom12010138
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipopolysaccharide, Derived from Various Bacterial Species, in Pulpitis—A Systematic Review

Abstract: Lipopolysaccharide (LPS) is widely used for induction of inflammation in various human tissues, including dental pulp. The purpose of this study was to summarize current medical literature focusing on (1) cell types used by researchers to simulate dental pulp inflammation, (2) LPS variants utilized in experimental settings and how these choices affect the findings. Our study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We searched for studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 121 publications
0
14
1
Order By: Relevance
“…We then indirectly verified our findings in LPS-stimulated macrophages in vitro to examine the suppression effects of EGCG on the LPS-like responses in COVID-19. Finally, our study is slightly different from the abovementioned literature (61)(62)(63)(64)(65)(66)(67) in terms of molecular signaling pathways. Based on the results of the bioinformatics analysis, we focused on the most credible MAPK (ERK1/2-JNK-P38) signaling pathway.…”
Section: Discussioncontrasting
confidence: 59%
“…We then indirectly verified our findings in LPS-stimulated macrophages in vitro to examine the suppression effects of EGCG on the LPS-like responses in COVID-19. Finally, our study is slightly different from the abovementioned literature (61)(62)(63)(64)(65)(66)(67) in terms of molecular signaling pathways. Based on the results of the bioinformatics analysis, we focused on the most credible MAPK (ERK1/2-JNK-P38) signaling pathway.…”
Section: Discussioncontrasting
confidence: 59%
“…We then indirectly verified our findings in LPS-stimulated macrophages in vitro to examine the suppression effects of EGCG on the LPS-like responses in COVID-19. Finally, our study is slightly different from the abovementioned literature ( 61 67 ) in terms of molecular signaling pathways. Based on the results of the bioinformatics analysis, we focused on the most credible MAPK (ERK1/2-JNK-P38) signaling pathway.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, EGCG-modified collagen membranes have been shown to downregulate the expression of inflammatory factors and promote M2 (CD163 and CD206) macrophages ( 66 ). EGCG also stimulates LC3-II production and autophagosome formation and inhibits LPS-induced upregulation and extracellular release of HMGB1 ( 67 ). Our results are consistent with those described above; however, the origins of the abovementioned research and our study are different.…”
Section: Discussionmentioning
confidence: 99%
“…As LPSs of different bacteria have been used in these studies, it is imperative to understand the discrepancy of the inflammation-inducing property between E. coli and P. gingivalis LPSs when interpretting and comparing these results. According to a most recently published systematic review [ 35 ], despite 105 in vitro studies using LPS in induction of pulp cell inflammation have been reported so far, only 2 experiments adopted both E. coli and P. gingivalis LPSs in stimulating heterogenous dental pulp cells [ 36 , 37 ]. Moreover, scarce evidence exists comparing the inflammatory effects of E. coli and P. gingivalis LPS on DPSCs.…”
Section: Introductionmentioning
confidence: 99%